(untitled) (World Bulletin of Public Health, 2025)
This article is dedicated to the analysis of Shenleyn-Genox disease (ShGD) – hemorrhagic vasculitis, a condition that leads to damage in the microcirculatory system, affecting the skin, joints, gastrointestinal tract, and kidneys. The disease is most common in children, with an incidence rate of 3-26.7 cases per 100,000 children. ShGD is characterized by the deposition of immune complexes consisting of immunoglobulin A (IgA), which leads to damage in blood vessels and tissues. The article discusses the disease’s pathogenesis mechanisms, clinical manifestations, diagnostic methods, and treatment approaches, emphasizing the importance of assessing the disease’s activity and selecting effective treatments. The development of the disease may be influenced by genetic and infectious factors. Currently, further research is required to better understand the full pathogenesis of the disease and improve treatment strategies. Additionally, the article highlights the existence of new diagnostic criteria and ongoing questions regarding the effectiveness of treatment